PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU SMA KABUPATEN MOJOKERTO - Hanif, Ma'mun; Rozi, Mochammad Fachrur (Department of Islamic Education Management, 2024)
This research was conducted to determine the influence of school principal leadership on the performance of secondary school teachers in Mojokerto Regency. There are 39 public and private high schools with 1,510 working teachers. These secondary schools are located in 19 sub-districts. This research includes quantitative causal relationships with library research methods using data collection techniques, or analytical review and review of previous research related to the influence of school principal leadership on teacher effectiveness. Research findings show that teacher efficacy has a positive and significant impact on principal leadership.